Peningkatan Hasil Belajar Matematika Melalui Model PBL dengan Metode Demonstrasi pada Siswa Sekolah Dasar - Asma'ul Khusnatin (Jurnal Didaktika Pendidikan Dasar, 2024)
Based on the results of observations at Bandung 2 Public Elementary School, Jombang district, it showed that there were low student learning outcomes, especially in folding and rotating symmetry material. This research is a collaborative class action (PTKK) to improve mathematics learning outcomes in folding symmetry and rotational symmetry material using the PBL model through the demonstration method in class III SD Negeri Bandung 2 Jombang Regency in the 2022/2023 academic year. Data collection techniques used in this study are observation and tests. The research data were analyzed using descriptive-qualitative and descriptive-quantitative methods. The results of the study using the PBL model through the demonstration method in cycle I obtained a complete percentage of learning outcomes of 64%. Whereas in cycle II, the completeness of learning outcomes increased to 88%. In conclusion, the application of the PBL model through the demonstration method can improve the learning outcomes of class III students at SD Negeri Bandung 2, Jombang Regency.